Towards the Next Generation: A 4-Dimensional Approach to Operating System Design - S Talekar, Priyanka; Shukla, Anshika; Dave, Vani; Dhanush, Kotapati Venkata; Vishnu M, Vishnu M (Journal of Neonatal Surgery, 2025)
This paper, discuss the general design concept for operating systems called the 4- dimensional operating system (4D OS) that integrates the four essential dimensions of an operating system, including performance, usability, scalability, and security, to meet the growing demands on complex systems. Instead of decomposing aspects of the operating system as is typically done in traditional OS design, the 4D OS integrates these dimensions into a more flexible and resilient substrate to support extreme high-performance computing (HPC) workloads and dynamic workload variability. With its innovative process interaction and synchronization methods, the 4D OS increases system flexibility and offers attractive benefits in many sectors including finance, healthcare – any industry that relies heavily on cloud services. We then substantiate this approach through comparisons with existing systems and real-world case studies, illustrating its potential to enable revolutionary OS designs demanded by next-generation applications.